Clinical features of otolith organ-specific vestibular dysfunction. Issue 1 (January 2018) - Fujimoto, Chisato; Suzuki, Sayaka; Kinoshita, Makoto; Egami, Naoya; Sugasawa, Keiko; Iwasaki, Shinichi
Highlights: Otolith organ specific vestibular dysfunction (OSVD) in the presence of normal semicircular canal function was investigated. 37% of OSVD was idiopathic. The most common clinical manifestation in idiopathic OSVD was recurrent rotatory vertigo. Abstract: Objective: To elucidate the clinical features and vestibular symptoms of patients with otolith organ dysfunction in the presence of normal function of the semicircular canals. Methods: We reviewed the clinical records of 277 consecutive new patients with balance disorders who underwent testing of cervical and ocular vestibular evoked myogenic potentials (cVEMPs and oVEMPs) as well as caloric testing and video head impulse testing (vHIT). Results: We identified 76 patients who showed normal caloric responses and normal vHIT findings in each SCC plane, but abnormal responses in cVEMP and/or oVEMP testing. Benign paroxysmal positional vertigo (BPPV) was the most common diagnosis. 37% of patients could not be categorized into any of the established clinical entities that could cause a balance disorder and did not show sensorineural hearing loss. The most common clinical manifestation in the idiopathic cases was recurrent rotatory vertigo with a duration of 1–12 h. Conclusions: The most common diagnosis of otolith organ-specific vestibular dysfunction was BPPV. The most common clinical manifestation in the idiopathic cases was recurrent rotatory vertigo. Significance: Specific dysfunction of the otolith organs occurs in association with some of the undiagnosed patients with recurrent rotatory vertigo.